Protective effect of Sargassum fusiforme polysaccharides on H2O2-induced injury in LO2 cells - Li, Jiarui; Wang, Zhuo; Chen, Jianping; Luo, Baozhen; Chen, Xuehua; Li, Rui; Gao, Jialong; Liu, Xiaofei; Song, Bingbing; Zhong, Saiyi (Frontiers in Marine Science, 2023)
To investigate the in vitro antioxidant activity of crude polysaccharide from Sargassum fusiforme (SFPS) and its protective effect against H2O2-induced injury in LO2 cells, SFPS was extracted from Sargassum fusiforme using water extraction and alcohol precipitation. High-performance liquid chromatography (HPLC) was used to measure its monosaccharide composition. The in vitro antioxidant activity of SFPS was evaluated using scavenging 1,1-diphenyl-2-picrylhydrazyl (DPPH) and hydroxyl radical assays. Moreover, its hepatoprotective activity was examined by establishing H2O2-induced LO2 cells injury model. The results showed that the SFPS was composed of Glc, Ara, Fuc, Gal, Man, Rha and Xyl. Meanwhile, SFPS exhibited strong antioxidant activity and potential hepatoprotective effect. Further studies found that SFPS could alleviate LO2 cells injury induced by H2O2 via decreasing malondialdehyde (MDA) and lactate dehydrogenase (LDH) levels, increasing superoxide dismutase (SOD) and catalase (CAT) activities and inhibiting intracellular reactive oxygen species (ROS) production. These results revealed that SFPS had the ability to protect the liver cells from H2O2-induced liver injury through its antioxidant activity.